Identifikasi Faktor Risiko Fisik di Ruang Penyimpanan Rekam Medis Rumah Sakit Islam Jakarta Pondok Kopi - Vickriyal Nadith; Muhammad Rezal; Nanda Aula Rumana; Muhammad Fuad Iqbal (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
In hospitals various types of services are provided including medical records management. Every job carries risks, and understanding and managing these risks requires a comprehensive risk identification process. This study focuses on investigating the physical risk factors in the medical storage rooms at Jakarta Islamic Hospital Pondok Kopi. Key aspects evaluated include room size, distance between rooms, temperature, and lighting conditions. The research method consists of direct observations and measurements of physical parameters in three interconnected archive rooms. The results reveal that the size of the storage room is constrained by the room's dimensions and excessive shelving, which limits staff efficiency in managing medical records. Furthermore, the proximity of rooms complicates accessibility for staff, highlighting the need for better spatial arrangements to improve operational efficiency and reduce the risk of accidents. Temperature assessments show a range of 29.0°C to 30.3°C, exceeding the Indonesian Ministry of Health's 2023 standards. The recommended storage temperature is between 22°C to 26°C with a humidity level of 25% to 55%. These elevated temperatures increase the risk of data damage and discomfort for staff. While lighting conditions generally meet standards, further evaluation is required to ensure optimal, consistent lighting. This study aims to improve storage organization, regulate temperature, and enhance lighting to optimize medical record management in hospitals, ensuring a safer, more efficient working environment for staff.